Expression of Emotional Intelligence Among Tennis Players (Baltic Journal of Sport and Health Sciences, 2020)
Background. Emotional intelligence (EI) is most commonly studied based on the cognitive-emotional ability or trait emotional self-efficacy model (Siegling & Petrides, 2015). This study was based on the EI capability model. Research based on ability models measures a person’s ability to solve emotional problems and assesses the ability to perform emotion-related tasks (Magrum, Waller, Campbell, & Schempp, 2019). The aim of this study was to reveal the expression of emotional intelligence in tennis players.Methods. To collect data, Schutte SSRI questionnaire survey was applied. Research participants were 99 tennis payers (55 men and 44 women, aged 15 to 65 years), including 85 amateurs and 15 professional players.Results. The comparison of mean scores for emotional intelligence according to gender showed that women had a statistically significantly higher score in other people’s emotion management (3.8 ± 0.44) than men (3.6 ± 0.49) (t(97) = –2.116; p = .037). Age comparisons of emotional intelligence scores revealed a statistically significant better estimate among tennis players over the age of 41 (4.24 ± 0.53) than those under the age of 30 (3.78 ± 0.7) (p = .008). There were also statistically significant positive weak relationships between tennis player age and emotion utilization (r = .269; p = .007) and overall emotional intelligence rating (r = .211; p = .036). There were no statistically significant differences between the aspects of emotional intelligence in training duration (p > .05).Conclusions. It was found that women believed they were better able than men to manage other people’s emotions, and the difference between women’s and men’s opinions was statistically significant (p < .05). Statistically significant positive correlations were revealed between the age of tennis players and the use of emotions (p < .01) as well as age and the general assessment of emotional intelligence (p < .05). This study did not reveal a significant relationship between the emotional intelligence of tennis players and the duration of training (p > .05). Keywords: tennis players, emotional intelligence, abilities.